Effect of Oral Vasopressors Used for Liberation from Intravenous Vasopressors in Intensive Care Unit Patients Recovering from Spinal Shock: A Randomized Controlled Trial - Ahmed Talaat Ahmed Ali; Mervat Anwar Abd EL-Aziz; Ahmed Mohamed Abdelhafez; Amr Mohamed Ahmed Thabet (Critical Care Research and Practice)
Background. Early vasopressor utilization has been associated with improved outcomes of patients with spinal shock; however, there are difficulties in weaning off vasopressors, in which patients after recovery from spinal shock develop a state of persistent vasodilation, which may take a few days to resolve and delays the discharge in the intensive care unit (ICU). Therefore, we tested the hypothesis using two oral vasopressors (midodrine and minirin) to facilitate weaning off intravenous vasopressors, reducing the ICU length of stay, and compare them for more efficacy. Methods. A randomized controlled trial was conducted in the trauma ICU at the Assiut University Hospital in Egypt in patients with spinal shock who required intravenous vasopressor for ≥24 h. A convenience sample was classified into three groups, in which 30 patients were included for each group. The midodrine group received midodrine 10 mg per oral every 8 h with gradual weaning off intravenous (IV) vasopressor (noradrenaline) after receiving 4 doses, the minirin group received minirin 60 μg per oral every 8 h with gradual weaning off IV vasopressor after receiving 4 doses, whereas the control group received IV vasopressor (noradrenaline) with gradual weaning according to the routine hospital care without adding oral vasopressors. The primary outcome was shortening the duration of IV vasopressor requirements. The secondary outcome was reducing the ICU length of stay. Results. Our results showed that the duration of IV vasopressor requirements in the midodrine (3.3 ± 1.32) and minirin groups (4.8 ± 1.83) was significantly lower than in the control group (6.93 ± 2.32). Additionally, the ICU length of stay (days) in the midodrine (5.13 ± 1.83) and minirin groups (5.5 ± 1.91) was significantly lower than in the control group (9.03 ± 3.74). Conclusion. Midodrine and minirin accelerated liberation from intravenous noradrenaline and effective in reducing the ICU length of stay in patients with spinal shock.